Efficacy and safety of ERCP in patients with gastroesophageal varices. Issue 37 (11th September 2020) - Hong, Junbo; Zuo, Wei; Wang, Anjiang; Zhu, Liang; Zhou, Xiaodong; Zhou, Xiaojiang; Li, Guohua; Liu, Zhijian; Liu, Pi; Zhen, Hao; Zhu, Yong; Ma, Jiuhong; et al.
Abstract : Abstract: Addressing pancreaticobiliary disorders concomitant with gastroesophageal varices remains challenging. The goal of this study was to evaluate and compare the efficacy and safety of endoscopic retrograde cholangiopancreatography (ERCP) in cirrhotic and noncirrhotic patients with gastroesophageal varices. We retrospectively analyzed the data of consecutive patients with gastroesophageal varices who underwent ERCP. Two hundred seventy ERCP procedures were performed on 208 patients. The overall technical success rate was 98.5%, and no difference was found between cirrhotic and noncirrhotic patients (98.7% vs 97.7%, P  = .511); of these, endoscopic retrograde biliary drainage, endoscopic metal biliary endoprosthesis placement, endoscopic retrograde pancreatic drainage, and stone extraction were conducted in 173/270 (64.1%), 27/270 (10.0%), 26/270 (9.6%), and 116/270 (43.0%) cases, respectively. Endoscopic retrograde biliary drainage and stone extraction were more frequently performed in cirrhotic cases (67.7% versus 45.5%, P  = .005; 46.5% versus 25.0%, P  = .009, respectively), while the noncirrhotic group had significantly higher rates of endoscopic metal biliary endoprosthesis placement (31.8% versus 5.8%, P  = .000) and endoscopic retrograde pancreatic drainage (18.2% versus 8.0%, P  = .036) than the cirrhotic group. The overall rate of adverse events was 21.1%, including fever (6.7%), post-ERCP pancreatitis ( 3.0%), hyperamylasemia (6.3%), duodenal papilla bleeding (3.3%), cardiac mucosal laceration (1.1%), and perforation (0.4%). No differences in any of the adverse events were found between the 2 groups. Additionally, gastroesophageal variceal bleeding occurred in 1 patient with grade III varices 7 days after ERCP. ERCP may be effective and safe for patients with gastroesophageal varices, irrespective of the etiologies caused by liver cirrhosis.